P183 Endobronchial Ultrasound And Tuberculosis: Beware The Non-caseating Granuloma. (10th November 2014) - Murray, J; Repossi, AC; Ismail, S; Bhowmik, A; Bothamley, GH
Abstract : Introduction: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is now the standard of care for investigating intra-thoracic lymphadenopathy. Although well validated in malignancy and sarcoidosis, the literature for intra-thoracic tuberculous lymphadenitis is limited. Previous work from neighbouring London boroughs reported a sensitivity (histology or microbiology consistent with tuberculosis (TB)) for TB of 94% with positive TB culture in 47% of 156 patients Methods: We examined retrospectively all EBUS-TBNA procedures performed at a London district general hospital between April 2010 and January 2014. Patients were referred to our EBUS service from our own hospital and two local centres. All patients were assessed clinically prior to the procedure and underwent a CT scan. Bronchoscopy reporting software was used to identify all EBUS procedures. Patient notes, clinic letters, electronic patient records and the London TB Register (LTBR) were used to obtain clinical information then matched with pathological and microbiological results. All patients were followed up for a minimum of 6 months. Results: 363 patients were included. The overall sample yield (either lymph node or tumour identified) was 94%. 63 cases of tuberculosis were identified and EBUS-TBNA had been diagnostic in 57 (90%). Pathological findings were consistent with TB in 84% of cases and culture was positive in 62%. Culture identified 5 cases of drug resistance. Where caseating granulomas were identified, 18/25 cases were culture positive and 15/23 where non-caseating granulomas were identified (p = 0.76). In addition, where necrotic material was obtained 3/5 samples were culture positive and where reactive lymph nodes were identified 4/9 samples were culture positive. Conclusion: EBUS-TBNA is a useful tool in the investigation of intra-thoracic tuberculous lymphadenitis. We show the possibility of achieving higher culture positivity from that reported in the literature. It highlights the importance of the TB culture for definitive diagnosis and detecting drug resistance. It is important to examine these findings in the context of appropriate clinical information and investigations.